Prognostic value of microRNAs in heart failure: A meta-analysis. Issue 46 (19th November 2021) - Yang, Jie; Yang, Xue-Song; Fan, Shao-Wei; Zhao, Xiao-Yu; Li, Chao; Zhao, Zheng-Yao; Pei, Hui-Juan; Qiu, Lu; Zhuang, Xin; Yang, Chuan-Hua
Abstract: Background: Reported studies have shown that expression levels of microRNAs (miRNAs) are related to survival time of patients with heart failure (HF). A systematic review and meta-analysis were conducted to study circulating miRNAs expression and patient outcome. Methods: Meta-analysis estimating expression levels of circulating miRNAs in HF patients from January 2010 until June 30, 2018, through conducting online searches in Pub Med, Cochrane Database of Systematic, EMBASE and Web of Science and reviewed by 2 independent researchers. Using pooled hazard ratio with a 95% confidence interval to assess the correlation between miRNAs expression levels and overall survival. Results: Four relevant articles assessing 19 circulating miRNAs in 867 patients were included. In conclusion, the meta-analysis results suggest that HF patients with low expression of serum miR-1, miR-423-5p, miR-126, miR-21, miR-23, miR-30d, miR-18a-5p, miR-16-5p, miR-18b-5p, miR-27a-3p, miR-26b-5p, miR-30e-5p, miR-106a-5p, miR-233-3P, miR-301a-3p, miR-423-3P, and miR-128 have significantly worse overall survival ( P   <   .05 ). Among them, miR-18a-5p, miR-18b-5p, miR-30d, miR-30e-5p, and miR-423-5p are strong biomarkers of prognosis in HF.